2011
DOI: 10.1021/am200406k
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Calcium Organophyllosilicates: Synthesis and In vitro Cytotoxicity Study

Abstract: Synthesis of multifunctional hybrid nanomaterials for biomedical applications has received great attention. Herein, we examine the potential toxicity of organophyllosilicates on cells from different organs such as A549 (lung epithelial cancer), HT-29 (colon epithelial cancer), MRC-5 (lung fibroblast) and CCD-986sk (skin fibroblast) cells. For this, aminopropyl functionalized magnesium phyllosilicate (AMP clay) and aminopropyl functionalized calcium phyllosilicate (ACP clay) were prepared using one-pot direct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 45 publications
5
65
0
1
Order By: Relevance
“…14 Given that the AMP clay is a nontoxic host material, 14 the in vitro and in vivo observation in the present study strongly support that AMP clay might have a high potential as a drug delivery carrier to improve the bioavailability of poorly soluble drugs.…”
Section: In Vivo Pharmacokinetic Studiessupporting
confidence: 58%
See 2 more Smart Citations
“…14 Given that the AMP clay is a nontoxic host material, 14 the in vitro and in vivo observation in the present study strongly support that AMP clay might have a high potential as a drug delivery carrier to improve the bioavailability of poorly soluble drugs.…”
Section: In Vivo Pharmacokinetic Studiessupporting
confidence: 58%
“…14 In the concentrations up to 500 µg/mL, the toxicity of AMP clay in terms of cell viability and membrane damage appeared to be minimal. In addition, AMP clay did not induce apoptosis even at concentrations as high as 1,000 µg/mL, implying that the potential toxicity of AMP clay is low.…”
Section: In Vivo Pharmacokinetic Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…MgAC has been applied for several environmental applications, e.g. soilflushing agent [22], flocculant [23], etc., and it has been reported not to have cytotoxicity to animal cells [24] and aquatic ecotoxicity towards marine bacteria, microalgae, and daphnia [25]. MgAC coated nZVI showed increased feasibility, compared to uncoated nZVI, for applications in water treatment, where high stability and mobility as well as high reactivity for degradation of contaminants are desired.…”
Section: Introductionmentioning
confidence: 99%
“…Although organoclays are commercially available for a variety of applications, such as the production of nano-sized materials, only few studies have been conducted on their toxicity. Han et al, [21] working on cells from different organs concluded that the toxicity of two organoclays on the viability and membrane damage was not severe. Contrasting results were obtained by Lordan et al [22] in experiments aimed to assess the cytotoxicity of a montmorillonite and an organically modified clay by measuring liver cells function and membrane integrity.…”
Section: Introductionmentioning
confidence: 99%